The energy that drives human networked organizations: a model for leading schools to thrive in complex times - Snyder, Karolyn J.; Snyder, Kristen Michelle; Mårtensson, Anna (Frontiers in Education, 2025)
PurposeDeveloping organizational adaptability to address sustainable development requires bold new management in education, school leaders are challenged to meet this paradigm shift amidst traditions of Newtonian views of organizing and industrial-based bureaucracy. Using Quantum physics as a theoretical lens, the authors introduce a model for leading schools as human-networked organizations, enabling them to become more responsive and adaptive to the evolving needs of students, businesses, and society.MethodsThe model is derived from an ethnography study of a private school in the United States, in which an existential-phenomenological approach, inspired by the work of Heidegger, was used to examine how educators describe the experience of working in a Human Networked Organization. The aim was to explore the phenomenon of magical energy that exists within this type of organizational structure to support its growth and sustainability over time.ResultsFindings highlight the critical role of teamwork, strong relationships, continuous professional development, trust, and respect with shared leadership for sustaining a culture of interconnections that can help schools thrive and be responsive in complexity. The model for leading schools as human networked organizations integrates six main features that are visualized using energy from the atom as a metaphor to reflect the interconnections between functions and culture to promote adaptability and responsiveness.DiscussionHelping educational leaders shift from a Newtonian View of organizing to a System’s View requires knowledge about energy systems. Quantum physics contributes insights that will assist educators in acquiring the knowledge and skills for leading in the 21st century.